Acute anoxic changes in peripheral nerve: anatomic and physiologic correlations. Issue 7 (6th May 2015) - Punsoni, Michael; Drexler, Steven; Palaia, Thomas; Stevenson, Matthew; Stecker, Mark M.
Abstract Introduction The response of the peripheral nerve to anoxia is modulated by many factors including glucose and temperature. The purposes of this article are to demonstrate the effects of these factors on the pathological changes induced by anoxia and to compare the electrophysiologic changes and pathological changes in the same nerves. Methods Sciatic nerves were harvested from rats and placed in a perfusion apparatus where neurophysiologic responses could be recorded continuously during a 16 h experiment. After the experiment, light microscopy and electron microscopy were performed. Results Light microscopic images showed mild changes from anoxia at normoglycemia. Hypoglycemic anoxia produced massive axonal swelling while hyperglycemic anoxia produced apparent changes in the myelin. Anoxic changes were not uniform in all axons. Electron microscopy showed only minor disruptions of the cytoskeleton with anoxia during normoglycemia. At the extremes of glucose concentration especially with hyperglycemia, there was a more severe disruption of intermediate filaments and loss of axonal structure with anoxia. Hypothermia protected axons from the effect of anoxia and produced peak axonal swelling in the 17–30°C range. Conclusions The combination of hyperglycemia or hypoglycemia and anoxia produces extremely severe axonal disruption. Changes in axonal diameter are complex and are influenced by many factors.